The Interaction of Hydrogen with the van der Waals Crystal γ-InSe - James Felton; Elena Blundo; Sanliang Ling; Joseph Glover; Zakhar R. Kudrynskyi; Oleg Makarovsky; Zakhar D. Kovalyuk; Elena Besley; Gavin Walker; Antonio Polimeni; Amalia Patané (Molecules, 2020)
The emergence of the hydrogen economy requires development in the storage, generation and sensing of hydrogen. The indium selenide ( <semantics> γ </semantics> -InSe) van der Waals (vdW) crystal shows promise for technologies in all three of these areas. For these applications to be realised, the fundamental interactions of InSe with hydrogen must be understood. Here, we present a comprehensive experimental and theoretical study on the interaction of <semantics> γ </semantics> -InSe with hydrogen. It is shown that hydrogenation of <semantics> γ </semantics> -InSe by a Kaufman ion source results in a marked quenching of the room temperature photoluminescence signal and a modification of the vibrational modes of <semantics> γ </semantics> -InSe, which are modelled by density functional theory simulations. Our experimental and theoretical studies indicate that hydrogen is incorporated into the crystal preferentially in its atomic form. This behaviour is qualitatively different from that observed in other vdW crystals, such as transition metal dichalcogenides, where molecular hydrogen is intercalated in the vdW gaps of the crystal, leading to the formation of “bubbles” for hydrogen storage.